Pemberdayaan Perempuan Dasawisma Melalui Inovasi Produk Wedang Jahe Instan Berbasis Potensi Lokal Di Nagari Pangian Kabupaten Tanah Datar - Syaiful, Ferry Lismanto; Yalfi, Nadhirah Ramadhani; Mukhsin, Aisya (LPPM Universitas Andalas, 2025)
Women’s empowerment is a vital strategy in strengthening household economic resilience and promoting sustainable social development. This study aims to enhance the capacity of the Dasawisma women’s group in Nagari Pangian by transforming local ginger (Zingiber officinale) into a high-value instant ginger drink product. The activity employed a Participatory Action Research (PAR) approach, emphasizing active participation of the community throughout all stages, including education, practical training, production assistance, packaging, and evaluation of learning outcomes and entrepreneurial motivation. A total of 20 participants took part intensively through three main stages: knowledge dissemination, technical training, product processing, packaging, and evaluation. Data were collected through pre-test and post-test assessments, skill observations, and entrepreneurship motivation questionnaires. The results showed a significant increase in participants’ knowledge, from an average score of 52 (low category) to 86 (high category), indicating a 65.4% improvement. Moreover, 85% of participants were able to independently produce instant ginger drink that met basic quality standards, with good sensory characteristics and a storage stability of up to six months. Beyond technical outcomes, the activity fostered social transformation by increasing participants’ confidence, group solidarity, and entrepreneurial awareness. The implementation of appropriate technology based on local potential through the PAR approach proved effective in transforming ginger from a subsistence commodity into a value-added product. This empowerment model could be replicated in other rural communities to promote bio pharmaceutical downstream development, strengthen household economies, and advance women’s independence based on local wisdom.